ANALYSIS OF STRATEGIC POSITIONING ON ORGANIZATION PERFORMANCE OF MOBILE TELECOMMUNICATION FIRMS IN NAIROBI COUNTY KENYA - GLORIAH, KUGUN; WANYONYI, Dr. KADIAN WANYAMA; SIALO, MR. FELIX; SANGORO, MR. OSCAR (IJRDO - Journal of Business Management, 2016)
The telecommunications industry has undergone dramatic shifts in its evolution. Since the end of the long-distance monopolies in the early 1980s and local monopolies in 1996, the industry has seen deregulation, innovation strategy, and new market entrants. Furthermore, the study was grounded on Diffusion Innovation Theory and the conceptual framework. The study adopted a descriptive and correlational research designs. Target population of this study comprised of 12,561 employees from Information Technology, Marketing and Procurement Departments: (Safaricom-6,500, Airtel-1,810 and Orange-4,251. The researcher then purposively select 10 managers from Safaricom Company Limited, 10 managers from Airtel and 10 managers from Orange Kenya. The 109 employees were selected through simple random sampling. Primary data was collected using questionnaires and interview schedules. The instruments was validated and tested for reliability through pilot testing. Quantitative data was analysed by use of descriptive and inferential statistics. Qualitative data from the in-depth interviews and focused group discussion were also analyzed and presented appropriately. For the study, the results indicated that innovation strategy had a statistically significant strong effect on the performance (R=0.715) and explained 51.2% of its variation (R2=.512, P=0.000). The results indicated that Marketing strategy had a statistically significant effect on the performance (R=0.773) and explained 59.7% of its variation (R2=.597, P=0.000). The unstandardized regression coefficient (β) value of the Marketing strategy was 0.956 with a t-test of 12.229and significance level of p-value=.000. The inferential results indicated that transformational leadership had a statistically significant effect on the performance (R=0.452) and explained 30.4% of its variation (R2=.204, P=0.000). Lastly, supply chain integration had significant relationship with the performance of sampled telecommunication firms in Kenya. This was achieved through affordable cost, conducive environment, distribution of services and clear logistics strategic plan. However, majority of the respondents disagreed that their organization is currently doing business with companies globally